PENEGAKAN HUKUM BAGI WARGA NEGARA YANG MEMILIKI IDENTITAS KEPENDUDUKAN GANDA MENURUT UNDANG-UNDANG NOMOR 24 TAHUN 2013 TENTANG ADMINISTRASI KEPENDUDUKAN - Putri, Shafira Rizqyta Amalia; Amarini, Indriati (Collegium Studiosum Journal, 2025)
This study discusses law enforcement against citizens who have dual citizenship based on Law Number 24 of 2013 concerning Population Administration. The research method used is a normative juridical approach, by analyzing laws and regulations, legal literature, policy documents, and scientific works that are relevant to the content and discussion. The results of the study show that the ownership of dual identities is still a serious problem in the administrative system in Indonesia which occurs as a result of the weakness of the existing population information and administration system and then becomes a gap for irresponsible individuals to commit a violation of duplication of population identity, and lack of legal awareness of the importance of maintaining identity documents belonging to each individual. to misuse of identity for personal gain. Law enforcement is carried out through administrative mechanisms such as biometric verification and clarification, and can be followed with appropriate sanctions if elements of intentionality are found. The main obstacles in its implementation include limited infrastructure for the government to reach remote areas, human resources, and weak data integration between agencies. Therefore, it is necessary to strengthen technical regulations, update the SIAK system, increase legal literacy in the community, and synergy across institutions to ensure administrative order and social justice based on a single identity.